The heterogenization of tumour cells with tuberculin. II. Studies of the antigenicity of tuberculin-heterogenized murine tumour cells in syngeneic BCG positive and BCG negative mice. - Vyakarnam, A (1981)
The possibility of enhancing the antigenicity of tumour cells by chemically attaching purified protein derivative (PPD) of tubercle bacillus as an immunogenic carrier determinant into the tumour cell surface has been explored in these studies. It was observed that multiple immunizations with PPD-coupled tumour cells did potentiate a marked anti-rumour response even to tumours that were very weakly antigenic. Moreover, such immunizations could be used to retard the growth of tumours in previously unimmunized animals. An attempt has been made to elucidate the important factors involved when PPD heterogenized tumour cells are used for immunization.